Efektifitas Tepid Sponge Bath Suhu 32oC dan 37oC dalam Menurunkan Suhu Tubuh Anak Demam - Kusnanto Kusnanto; Ika Yuni Widyawati; Indah Sri Cahyanti (Universitas Airlangga, 2008)
Introduction: Tepid sponge bath is a therapeutic bath by washing all around of the body with warm water to decrease body temperature. Warm water that used were 32oC (nail warm) and 37oC (warm). The aimed of this study was to compare the effectivity of tepid sponge bath with 32oC and 37oC warm water on decreasing body temperature at toddler with fever.Methods: A quasy experimental pre post test design was used in this study. The population was toddler who had body temperature ≥38oC which treated in anggrek pediatric room dr. Iskak public hospital Tulungagung. There were 26 respondents recruited by using purposive sampling technique and divided into two group, each of 13 respondents received tepid sponge bath with 32oC and others received tepid sponge bath with 37oC warm water. The independent variable was tepid sponge bath and dependent variable was body temperature. Data were collected by using digital termometere and noted in respondent observation, then analyzed by using Paired t-Test and Mann Withney U-Test.Results: The result showed that there was an effectivity on decreasing body temperature by giving tepid sponge bath with 32oC and 37oC warm water with significance level p=0.000 and there was a difference decreasing body temperature among both of them with significance level p=0.016.Conclusion: It can be concluded that tepid sponge bath with 37oC warm water was more effective than tepid sponge bath with 32oC warm water. Further studies should be observed the effectivity of tepid sponge bath with more specific age, fever character and more time and respondent.